How to see, how to draw : keys to realistic drawing - Nice, Claudia , 1948- (North Light Books, 2016)
This book begins with learning how to observe- to see what's really there, not what you want to see. Observation is a skill thats learned and practiced, and one of the hallmarks of successful artists is that they know how to look at a subject with clear vision unfettered by preconceived notions or old habits. Using reference photos, diagrams, sketches and comparative examples, the author shows you first how to observe an object, and second how to translate that observation into an accurate rendering using graphite pencils, charcoal pencils and pen and ink